Analisis Persamaan dan Perbedaan Putusan Penolakan Gugatan Wanprestasi (Studi Kasus: Putusan Pengadilan Negeri Yogyakarta Nomor 119/ Pdt.G /2015/PN.Yk dan Nomor 36/Pdt.G/2014/PN.Yk) - Yosa Raynaldi Maruli; Ning Adiasih (Jurnal Hukum Adigama, 2020)
Based on the judge in making the decision not to see the three elements will reduce the value of justice. In Case Decision Number 119/Pdt.G/2019/ PN.Yk between Urip Mulyo Cooperative and Mr. Kuntjoro. the case of default by Mr. Kuntjoro against the Urip Mulyo Cooperative, where Mr. Kuntjoro borrowed Rp. 78,000,000 with an interest of 3% per month for 3 months starting from May 20, 2010 to August 20, 2010 and if Mr. Kuntjoro had not been able to repay his debts during 3 months, Mr. Kuntjoro was fined 1/1000 per day from the remaining amount of the delayed payment. In Case Decision No.36 / Pdt.G / 2014 / PN.Yk, between Oentoeng Soedianto Sastro Dipoero against his legal counsel named Banu Tjahjo Nugroho, S.H., whose principal matter was the cancellation of the Power of Attorney and Honorarium agreement. Based on the contents in this thesis, there are problems as to how the analysis of the similarities and differences in the Decision on Rejection of Default Lawsuits (Case Study: Yogyakarta District Court Decision No 119 / Pdt.G / 2015 / PN.Yk and No. 36 / Pdt.G / 2014 / PN .Yk).